DIF (Differential Item Functioning) Analysis on the Self-Acceptance Scale Based on Al-Ghazali’s Theory Using the Rasch Model - Mawaddati, Ilmi; Suprananto (Arfannur: Journal of Islamic Education, 2026)
This study aims to develop and analyze a self-acceptance instrument based on Al-Ghazali’s theory using the Rasch Model approach, as well as to detect item bias or Differential Item Functioning (DIF) based on gender. The instrument was constructed based on four main aspects from Al-Ghazali’s theory: tawakal, syukur, sabar, ikhlas. The participants were 439 active ungraduate students of IAIN Pontianak in the 2024 academic year, selected using proportionate cluster random sampling technique. The content validity of the instrument items was tested using Aiken’s V formula, involving six experts and obtained an average value 0f 0.95, which is categorized as very high. Data analysis was conducted using the Winsteps software. The results showed that out of 43 items, several items were identified as having potential DIF. Specifically, in the aspects of tawakal (5 items), syukur (6 items), sabar (2 items), and ikhlas (1 items) indicating possible bias based on gender. This research is expected to serve as a foundation for developing Islamic psychology instruments that are more objective, contextual, and relevant for both modern scientific studies and the implementation of personality development or self-development programs for students, focusing on nurturing the character traits of tawakal, sabar, syukur, and ikhlas.